The Contribution From Social Media, Healthy Lifestyle, And Religion To Teacher Competence And Its Impact On Teacher Performance - Aindra, Alifah Diantebes; Wibawa, Aji Prasetya; Nurhadi, Didik; Ghosh, Anusua (Universitas Negeri Malang, 2023)
This study examines the contribution of social media, healthy lifestyle and religion to teacher competence and performance. Testing and data analysis techniques used path analysis. Using the technique of Purposive Consecutive Sampling within one month, the respondents obtained 189 teachers. Data collection techniques using questionnaires. Based on the results of the research that has been done, it can be said that social media, lifestyle, and religion contribute to teacher competence and impact teacher performance. However, when viewed partially, other findings show that social media only contributes to teacher competence. A healthy lifestyle contributes to teacher competence and teacher performance. In contrast, religious variables do not contribute to teacher competence and teacher performance, and teacher competence contributes to teacher performance. Based on the proposed relationship scheme, it was found that teacher competence could not mediate the relationship between independent variables and teacher performance